FOLFIRINOX versus gemcitabine plus nab-paclitaxel as the first-line chemotherapy in metastatic pancreatic cancer. (3rd October 2022) - Ay, Seval; Atcı, Muhammed Mustafa; Arıkan, Rukiye; Dülgar, Özgecan; Özyükseler, Deniz Tataroğlu; Paksoy, Nail; Doğan, İzzet and Öztosun, Buğra and Taştekin, Didem and Öven, Başak Bala and Gümüş, Mahmut
Abstract: Pancreas cancer (PCa) is one of the mortal cancer types with ranking as fourth leading cancer death in both sexes together. FOLFIRINOX (FFX) and Gemcitabine plus nab-paclitaxel (GNP) are approved as first-line metastatic treatment in PCa. The aim of this study was to compare the clinical outcomes, treated with FFX and GNP as first-line metastatic PCa. Medical records of patients diagnosed with metastatic PCa, from January 2010 to December 2020 were analyzed. This study was a retrospective cohort, multi-institution analysis. The focus of the present study was to compare the efficiency of FFX and GNP chemotherapy combinations in the first-line treatment of PCa. Efficacy had been measured by progression-free survival (PFS) and overall survival (OS). 182 patients diagnosed with PCa receiving metastatic first-line treatment were retrospectively analyzed. Patients were divided into two groups one hundred and three (56.6%) patients treated with FFX and seventy-nine (43.4%) patients treated with GNP. Patients in the FFX group were younger and had a better ECOG performance status. Overall response rate (ORR) was 69.9% in FFX and 37.9% in GNP group (p: 0.000). Disease control rate (DCR) was 73.7% in patients treated with FFX and 39.2% in GNP group (p: 0.000). The median PFS was 8.3 months (FFX 9.1 vs. GNP 6.7, HR = 0.25, 95% CI: 0.16-0.38) the median OS was 12.2 months (FFX 14.1 vs. GNP 9.6, HR = 0.48, 95% CI: 0.31-0.72). Guidelines recommend both FFX and GNP regimens as a first-line treatment of metastatic PCa. In clinical routine, it is still unclear which regiment is more effective. The present study showed increased survival parameters with FFX versus GNP with similar toxicity profiles.